Regulatory quality and corporate leverage: Evidence from a large international sample - Belaounia, Samia; Nguyen, Pascal; Rahman, Nahid; Zhao, Ruoyun (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2025)
Corporate leverage is strongly related to firm characteristics. However, this relationship varies across country-level institutions. In this study, we investigate whether country-level regulatory quality indirectly affects corporate leverage by moderating the effects of firm-level determinants of capital structure. Using a sample of 46,184 firms from 70 countries, we show that regulatory quality mitigates the positive influence of firm size and asset tangibility on leverage, while the negative influence of growth opportunities, R&D intensity, and profitability is similarly moderated. These results highlight the benefit of robust regulatory quality in facilitating the access to debt financing of small, R&D-intensive, and growth-oriented firms with few tangible assets.